2018
DOI: 10.1186/s12888-018-1627-9
|View full text |Cite|
|
Sign up to set email alerts
|

Dialectical behaviour therapy for treating adults and adolescents with emotional and behavioural dysregulation: study protocol of a coordinated implementation in a publicly funded health service

Abstract: BackgroundIn the Republic of Ireland, borderline personality disorder (BPD) is a feature of approximately 11–20% of clinical presentations to outpatient clinics within mental health services. These estimates are similar to other countries including the UK and USA. Dialectical behaviour therapy (DBT) is an intervention with a growing body of evidence that demonstrates its efficacy in treating individuals diagnosed with BPD. While a number of randomised controlled trials (RCTs) have demonstrated the efficacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…Measures were selected and compiled based on the four treatment targets of DBT. A detailed overview of treatment targets and corresponding measurement variables for this study are reported elsewhere (Flynn, Kells, Joyce, Suarez, & Gillespie, 2018). Six outcome measures were included in the current study Borderline Symptom List (BSL-23; Bohus et al, 2007): a 23-item self-report measure of borderline-typical symptomatology.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Measures were selected and compiled based on the four treatment targets of DBT. A detailed overview of treatment targets and corresponding measurement variables for this study are reported elsewhere (Flynn, Kells, Joyce, Suarez, & Gillespie, 2018). Six outcome measures were included in the current study Borderline Symptom List (BSL-23; Bohus et al, 2007): a 23-item self-report measure of borderline-typical symptomatology.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Therapist-reported measures. DBT therapists on each team completed therapist assessment forms developed by the research team to measure health service utilisation (Flynn, Kells, Joyce, Suarez et al, 2018). Data collected included presence and frequency of self-harm, emergency department (E.D.)…”
Section: Outcome Measuresmentioning
confidence: 99%
“…It is envisaged that our findings on the costs of treating BPD can be used alongside studies investigating the effectiveness of evidence-based treatments for BPD, such as DBT, schema therapy, mentalisation based therapy or transference focused psychotherapy (Departament de Salut Generalitat de Catalunya, 2011; Stoffers et al 2012). DBT is the recommended evidencebased treatment for persons with BPD (Government of Ireland, 2006), and is currently being implemented in Ireland through the National DBT Project (Flynn et al 2018b). Furthermore, these future studies can then inform the development of national guidelines that promote effective and cost-effective treatments for BPD, and inform budgeting and resource allocation decisions.…”
Section: Discussionmentioning
confidence: 99%
“…This paper is part of a larger study examining the effectiveness and cost-effectiveness of dialectical behaviour therapy (DBT) for treating individuals with BPD. The participants in this study include all recruited participants at baseline (see Flynn et al 2018b for study protocol). 1 Data collection occurred between February 2014 and March 2016.…”
Section: Data Collection and Samplementioning
confidence: 99%
“…Outcome measures for this study were chosen based on identification of clinically relevant constructs for both participant groups. These measures are a subset of a larger battery of measures used to evaluate DBT‐A as part of a coordinated implementation study (Flynn, Kells, Joyce, Suarez, & Gillespie, ). The outcome measures used for the comparison in this study were as follows:…”
Section: Methodsmentioning
confidence: 99%